2006
DOI: 10.1097/01.dad.0000154396.14971.aa
|View full text |Cite
|
Sign up to set email alerts
|

Bacillary Angiomatosis Associated With Pseudoepitheliomatous Hyperplasia

Abstract: Bacillary angiomatosis is an opportunistic bacterial infection caused by either Bartonella henselae or B. quintana. The classic histologic presentation of bacillary angiomatosis involves three components: a lobular proliferation of capillaries with enlarged endothelial cells, neutrophilic debris, and clumps of finely granular material identified as bacteria with staining techniques. Pseudoepitheliomatous hyperplasia is a histologic reaction pattern characterized by epithelial proliferation in response to a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A rare association between pseudoepitheliomatous hyperplasia and Bartonella infection has been reported in the medical literature. 11 This diagnosis was considered in the differential, but the pattern of infiltration by atypical squamous cells into the deeper stromal tissue confirmed that the underlying disease process was a malignancy and not reactive hyperplasia alone. Finally, it has also been demonstrated that Bartonella spp stimulate cellular proliferation and may lead to tumor formation.…”
Section: Discussionmentioning
confidence: 93%
“…A rare association between pseudoepitheliomatous hyperplasia and Bartonella infection has been reported in the medical literature. 11 This diagnosis was considered in the differential, but the pattern of infiltration by atypical squamous cells into the deeper stromal tissue confirmed that the underlying disease process was a malignancy and not reactive hyperplasia alone. Finally, it has also been demonstrated that Bartonella spp stimulate cellular proliferation and may lead to tumor formation.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3][4]7,8] Culture of biopsied tissues, electron microscopy (EM) examination, polymerase chain reaction, and serology are other procedures that can be used for BA diagnosis. [1,3,4,8,9] In particular, EM has been useful for confirming the identity of bacilli when staining techniques have been nondiagnostic. [9] The basic histological architecture of BA is a lobular proliferation of endothelium-lined blood vessels within the superficial dermis.…”
Section: Discussionmentioning
confidence: 99%
“…[1,3,4,8,9] In particular, EM has been useful for confirming the identity of bacilli when staining techniques have been nondiagnostic. [9] The basic histological architecture of BA is a lobular proliferation of endothelium-lined blood vessels within the superficial dermis. Numerous perivascular neutrophilic granulocytes, especially in deeper regions, are also typically present, together with diffuse formation of blood capillaries ("infectious angiogenesis").…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a vaguely lobulated intradermal proliferation of capillaries lined by plump, epithelioid endothelial cells, there are aggregates of polymorphonuclear leucocytes, with karyorrhectic debris and amphophilic extracellular aggregates of bacillary organisms in the intervening stroma 4 104 105. Rarely, BA is associated with pseudoepitheliomatous hyperplasia 106. WS staining will highlight the clumps of Bartonella organisms.…”
Section: Diagnostic Approachmentioning
confidence: 99%